Molecular and Clinical Characterization of a Novel Nonsense Variant in Exon 1 of the UPF3B Gene Found in a Large Spanish Basque Family (MRX82) - Tejada, María Isabel; Villate, Olatz; Ibarluzea, Nekane; de la Hoz, Ana Belén; Martínez-Bouzas, Cristina; Beristain, Elena; Martínez, Francisco; Friez, Michael J.; Sobrino, Beatriz; Barros, Francisco (Frontiers in Genetics, 2019)
X-linked intellectual disability (XLID) is known to explain up to 10% of the intellectual disability in males. A large number of families in which intellectual disability is the only clinically consistent manifestation have been described. While linkage analysis and candidate gene testing were the initial approaches to find genes and variants, next generation sequencing (NGS) has accelerated the discovery of more and more XLID genes. Using NGS, we resolved the genetic cause of MRX82 (OMIM number 300518), a large Spanish Basque family with five affected males with intellectual disability and a wide phenotypic variability among them despite having the same pathogenic variant. Although the previous linkage study had mapped the locus to aninterval of 7.6Mb in Xq24-Xq25 of the X chromosome, this region contained too many candidate genes to be analysed using conventional approaches. NGS revealed a novel nonsense variant: c.118C>T; p.Gln40* in UPF3B, a gene previously implicated in XLID that encodes a protein involved in nonsense-mediated mRNA decay (NMD). Further molecular studies showed that the mRNA transcript was not completely degraded by NMD. However, UPF3B protein was not detected by conventional Western Blo tanalysis at least downstream of the 40 residue demonstrating that the phenotype could be due to the loss of functional protein. This is the first report of a premature termination codon before the three functional domains of the UPF3B protein and these results directly implicate the absence of these domains with XLID, autism and some dysmorphic features.